Higher Frequency of HIV-1 Drug Resistance and Increased Nucleoside Reverse Transcriptase Inhibitor Mutations among the HIV-1 Positive Antiretroviral Therapy–Naïve patients Coinfected With Mycobacterium tuberculosis Compared With Only HIV Infection in India. (21st July 2018) - Sinha, Sanjeev; Gupta, Kartik; Khan, Nawaid Hussain; Mandal, Dibyakanti; Kohli, Mikashmi; Das, BK; Pandey, RM
Background: Emergence of human immunodeficiency virus (HIV) drug resistance mutations prior to highly active antiretroviral therapy is a serious problem in clinical management of HIV/AIDS. Risk factors for appearance of drug resistance mutations are not known. We hypothesize that Mycobacterium tuberculosis infection may contribute to rapid emergence of such mutations in antiretroviral therapy–naïve patients. Methods: A total of 115 patients were recruited in this study of which 75 were HIV+TB+ coinfected (group 1) and 40 were HIV+TB− (group 2). Blood samples from all the patients were collected and CD4+ cell counts; HIV-1 plasma viral load and sequencing of protease and two-third region of reverse transcriptase of HIV-1 was performed and analyzed for drug resistance pattern. Results: For patients with HIV+TB+, 10.6% (8/75) had mutations to non-nucleoside reverse transcriptase inhibitors (NNRTIs), 4% (3/75) to nucleoside reverse transcriptase inhibitors, and only 2.6% (2/75) patients had mutations to protease inhibitors. Interestingly, for group 2 (HIV+TB−), there were only NNRTI mutations found among these patients, and only 3 patients (7.5%) had these drug-resistant mutations. Clade typing and phylogenetic tree analysis showed HIV-1 subtype C predominance in these patients. Conclusions: Our study showed that higher percentage of HIV drug resistance mutations was found among HIV+TB+ individuals compared with tuberculosis-uninfected patients. Tuberculosis coinfection may be a risk factor for emergence of high frequency of drug resistance mutations. Studies with a larger sample size will help to confirm these findings from the Indian population.